Pain Management of Pediatric Musculoskeletal Injury in the Emergency Department: A Systematic Review - Sylvie Le May; Samina Ali; Christelle Khadra; Amy L. Drendel; Evelyne D. Trottier; Serge Gouin; Naveen Poonai (Pain Research and Management)
Background. Pain management for children with musculoskeletal injuries is suboptimal and, in the absence of clear evidence-based guidelines, varies significantly. Objective. To systematically review the most effective pain management for children presenting to the emergency department with musculoskeletal injuries. Methods. Electronic databases were searched systematically for randomized controlled trials of pharmacological and nonpharmacological interventions for children aged 0–18 years, with musculoskeletal injury, in the emergency department. The primary outcome was the risk ratio for successful reduction in pain scores. Results. Of 34 studies reviewed, 8 met inclusion criteria and provided data on 1169 children from 3 to 18 years old. Analgesics used greatly varied, making comparisons difficult. Only two studies compared the same analgesics with similar routes of administration. Two serious adverse events occurred without fatalities. All studies showed similar pain reduction between groups except one study that favoured ibuprofen when compared to acetaminophen. Conclusions. Due to heterogeneity of medications and routes of administration in the articles reviewed, an optimal analgesic cannot be recommended for all pain categories. Larger trials are required for further evaluation of analgesics, especially trials combining a nonopioid with an opioid agent or with a nonpharmacological intervention.